Development of a methodology for eliminating failures of an FDM 3D printer using a "failure tree" and FMEA analysis. Issue 1 (May 2021) - Zagidullin, R; Antipov, D; Dmitriev, A; Zezin, N
Abstract: The article presents a functional structural analysis of the design and software of an FDM 3D printer. On the basis of functional and structural analysis, a "failure tree" of the design of a 3D printer was built. An FMEA analysis was carried out to identify the reasons for the design failures of the 3D printer and develop recommendations for their elimination. The result of the FMEA analysis was the development of a method for eliminating design failures in FDM 3D printers.